Pelatihan Pembuatan Filter Anaerobik Untuk Septic Tank Dari Botol Bekas Di Desa Rasau Jaya 3 Kecamatan Rasau Jaya Kabupaten Kubu Raya - syarifah melly maulina; Ranty Christiana; Muji Listyo Widodo (Pengelola Jurnal Politeknik Negeri Ketapang, 2022)
Used plastic bottles are one of the wastes whose amount always increases every year, therefore an alternative use is needed, namely as a biofilter media. Biofilter is a biological treatment technology that utilizes microorganisms in treating wastewater. In a biofilter, media is needed as a place for bacteria to attach. Materials that can be used as biofilter media have certain criteria such as high intensity, high cavity volume fraction, large surface area, hydrophilic nature and so on. In order to reduce the negative impact of used plastic bottle waste, various types of technology for the use of plastic bottles were developed, including the use of plastic bottles as biofilter media. According to research conducted by (Putra & Karnaningroem, 2016) proving that used plastic bottles of probiotic drinks can reduce COD 73.24%-80.53%. The advantages of the biofilter process are the high efficiency of removing COD, BOD, and suspended solids, easy management, low operating costs, and relatively little sludge production compared to the activated sludge process (Said, Application of Bio-Ball for Biofilter Media Case Study Processing). Jeans Washing Wastewater, 2005). According to (Salas, 2016) Biofiltration is a processing activity in which absorption, oxidation and filtration of pollutants occur due to the activity of certain microorganisms in the biofilm. Biofilm is a biological slime layer that contains microorganisms (aerobic, anaerobic, facultative bacteria, fungi, and protozoa) that have the ability to degrade pollutants in wastewater. (Chaudhary, Vigneswaran, & H, 2003) Several criteria that can be met in determining the biofilter media according to (Said, Application of Bioball Filter Media, Case Study of Washing Wastewater Treatment, Jean, 2005) are materials that can be used as biofilter media having certain criteria such as inertia. high volume fraction, high cavity volume fraction, large surface area, hydrophilic nature, and so on are found in used plastic bottles so it is expected that used plastic bottles can be used as biofilter media and have high COD and BOD removal capabilities.)